GNOSEOLOGICAL ASPECT OF RESEARCH OF THE PROCESSES OF FORMATION AND DEVELOPMENT OF AUDIT AS A SCIENCE - Holyash, Iryna (Journal of European Economy, 2017)
The processes of development of audit as a science from the different viewpoints are considered. The attention to the key problems, which emerge while these processes of examination, is paid. Processes of development of audit are studied from the position of gnoseology. The interpretation of sciences which are presented in the works of famous scholars is given, the philosophical views on the science are considered, the criteria of scientific character are defined. All these facts are adapted to audit which can be considered as a science.